Construction supply chain management in the fourth industrial revolution era - Oluwasola Osunsanmi, Temidayo; Aigbavboa, Clinton; Thwala, Wellington; Oke, Ayodeji Emmanuel (Emerald Publishing, 2022)
Supply chain management in the construction industry has passed through different eras - yet throughout, the construction industry has experienced fragmentation, late project delivery and other Gordian Knots due to its slow adoption of innovative modern technologies and principles in the supply chain processes. Addressing the need to harmonise the construction supply chain and establish the industry as the lynchpin of the economy, Construction Supply Chain Management in the Fourth Industrial Revolution Era acts as a roadmap, re-aligning the activities of the construction supply chain stakeholders with the principles and tenets of Industry 4.0. Gathering evidence on both the benefits and disruptive potentials within the current construction supply chain management domain, this collection determines the acceptable practice and standard for regulatory bodies and managers, appealing also to researchers as it expands the frontiers of knowledge in the fourth industrial era.
Keywords: Industrie 4.0; Supply Chain Management; Bauwirtschaft; Industriestaaten; Entwicklungsländer; Construction industry / Management; Business logistics / Management; Business & Economics, Logistics & Supply Chain; Purchasing & supply management